A Masculinity of Gender Stereotypes in Brave Motion Picture - Dharpa Sugianto, Tirta Agraprana; Probowati, Yeni; Setyowati, Yulis (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2024)
Movies are a potent medium for learning, as they are not only accessible but also have the capability to shape behaviour and provoke meaningful conversations. It is crucial to recognize that not all cinematic content promotes positive examples; some scenes reinforce negative portrayals and harmful stereotypes. This study decisively examines the gender dynamics in the Walt Disney Company film